Cela n’arrivera pas - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Cela n’arrivera pas, un tremblement de terre aura déjà avalé cet endroit. 'Un pêcheur à Port Royal, Jamaïque, 1999.